Des tortues exotiques en ville : évaluation, perceptions et propositions de gestion à Strasbourg, France - Véronique Philippot; Sandrine Glatron; Adine Hector; Yves Meinard; Jean-Yves Georges (VertigO)
The threats to biodiversity lead us to reflect on the meaning we give to the invasive potential of exogenous species and to their management. The disconnection of urban dwellers from nature complicates the human - nonhuman relationships that we invite to think in terms of multispecific anthropology. The latter questions the forms of living together and leads us to examine how societies deal with the reception or the exclusion of species considered invasive. We studied exotical turtles found in two parks of Strasbourg with a double naturalistic and ethnological approach. More than 60 individuals from eight exotic turtle species have been contacted during the summers of 2017 and 2018. The shared opinions on the relevance of their presence reveal a certain embarrassment of the 87 informants. Turtles represent a factor of attraction and reconnection with nature but their exoticism questions or worries. This exotism invites us to confront the values attributed to them in order to reconsider the methods used to manage our environments. Once informed by the investigator about the origin and the invasive potential in the natural environment, the majority of users recommend the extraction of the turtles towards dedicated places, but the idea of their destruction is globally rejected. The carefull analysis of discourses points out to nuanced or perplexed postures on the legitimacy of humans to govern nature. More broadly, the relationship between city dwellers and the Nature or even Otherness is questions by these exotical turtles in our urban green parcs.